Clinical effects of Lactobacillus strains as probiotics in the treatment of irritable bowel syndrome. Results from the LAPIBSS trial: Future objectives - Maixent, Jean Michel; Pons, Olivier; Sennoune, Souad R.; Sadrin, Stéphane (Cellular and Molecular Biology, 2020)
The objective of this communication is to present and analyze the recent results from the LAPIBSS study in order to improve future clinical trials on the effects of Lactobacillus strains in the treatment of irritable bowel syndrome (IBS). Using a tightly-controlled clinical trial protocol with the highest Jadad score of 5/5, the current trial aimed to demonstrate the efficacy of a 2-strain mixture of Lactobacillus acidophilus (L. acidophilus) to improve IBS symptoms. Eighty patients diagnosed with IBS according to Rome III criteria were recruited to a multicentric, double-blind, in parallel groups, placebo-controlled, randomized clinical trial. Patients were provided with a daily dose of two capsules containing either two probiotic strains (5 x 109 cfu/capsule) or placebo for 8 weeks. The primary endpoint was abdominal pain score assessed with a 100-mm visual analogue scale (VAS). Secondary endpoints included scores of bloating, flatus and rumbling assessed with a 100-mm VAS, a composite score that consisted of the sum of the 4 VAS scores, and the stool frequency and consistency assessed with the Bristol Stool Form Scale. Our study has failed to demonstrate a significant improvement of the primary endpoint of abdominal pain. Significant differences between groups were observed for flatus score at week 4 (P=0.04) and week 8 (P=0.03) and for composite score at week 8 (P=0.04). The consumption of the 2-strain mixture of L. acidophilus over 8 weeks is safe, significantly decreases flatus and composite scores. The significant effect on flatus could result from the species-specific homofermentative properties of L. acidophilus strains. The negative results on abdominal pain and the gained experience are discussed for the future clinical trials in IBS.